Bio-SCAN V2: A CRISPR/dCas9-based lateral flow assay for rapid detection of theophylline - Jiang, Wenjun; Aman, Rashid; Ali, Zahir; Mahfouz, Magdy (Frontiers in Bioengineering and Biotechnology, 2023)
Rapid, specific, and robust diagnostic strategies are needed to develop sensitive biosensors for small molecule detection, which could aid in controlling contamination and disease transmission. Recently, the target-induced collateral activity of Cas nucleases (clustered regularly interspaced short palindromic repeats [CRISPR]-associated nucleases) was exploited to develop high-throughput diagnostic modules for detecting nucleic acids and small molecules. Here, we have expanded the diagnostic ability of the CRISPR-Cas system by developing Bio-SCAN V2, a ligand-responsive CRISPR-Cas platform for detecting non-nucleic acid small molecule targets. The Bio-SCAN device consists of an engineered ligand-responsive sgRNA (ligRNA), biotinylated dead Cas9 (dCas9-biotin), 6-carboxyfluorescein (FAM)-labeled amplicons, and lateral flow assay (LFA) strips. LigRNA interacts with dCas9-biotin only in the presence of sgRNA-specific ligand molecules to make a ribonucleoprotein (RNP). Next, the ligand-induced RNP is exposed to FAM-labeled amplicons for binding, and the presence of the ligand (small molecule) is detected as a visual signal ([dCas9-biotin]-ligRNA-FAM labeled DNA-AuNP complex) at the test line of the LFA strip. With the Bio-SCAN V2 platform, we successfully detected the model molecule theophylline with a limit of detection (LOD) up to 2 μM in a short time, requiring only 15 minutes from sample application to visual readout. Taken together, Bio-SCAN V2 device provides a rapid, specific, and ultrasensitive detection platform for theophylline.